Innovation in interactive learning methods to enhance student engagement and understanding in the classroom: a case study of 10th-grade students at Madrasah Aliyah - Wakib Kurniawan; Siti Rohmaniah; Maulana Yusuf Abdillah (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Low student engagement and understanding in the learning process is one of the main challenges in formal education today. Traditional learning methods that tend to be one-way are often unable to facilitate students' active participation, thus hindering the process of understanding the material optimally. This research aims to explore innovative interactive learning methods as a solution to improve student engagement and understanding in the classroom. The method used in this research is literature study and data analysis from observations in several schools that have implemented interactive learning techniques, such as group discussions, simulations, and the use of digital technology. The results showed that the implementation of interactive learning methods significantly increased student engagement by 40% compared to conventional methods. In addition, students' understanding of the subject matter increases along with the high participation in learning activities. The use of interactive media, such as learning videos and educational applications, also had a positive impact on students' motivation to learn more actively. The implication of this research shows that the integration of interactive learning methods in the curriculum can be an effective strategy in improving the quality of classroom learning and shaping a more dynamic learning environment.